Decay resistance between sapwood and heartwood of parashorea malaanonan / Mahmud Sudin and Razak Wahab - Sudin, Mahmud; Wahab, Razak (2004)
Parashorea malaanonan" (locally known as Urat Mata Daun Licin) is a high-quality commercial light hardwood in Sabah. The stem of the species however often considered as more prune to infection by wood degrading agents such as decay fungi and also stem borers, as compared to other species in the dipterocarp forest. In relation to this, variation in resistance between the outer and inner portions of the stem is a subject of interest. In this study, we used agar-block test method to measure the weight loss in the sapwood and heartwood of P. malaanonan following 12 and 24 weeks exposure to Gloeophyllum sp., which was isolated from decayed wound of the host species. Variation was observed in weight loss between the two wood types and in general weight loss was greater in the sapwood than the heartwood wood blocks tested. Mean weight loss was however differ significantly at 24 weeks incubation (38.9±0.I% and 28.3±0.1%, respectively). The result corresponds to the general understanding that thinner wood cell wall in the developing sapwood making it more easily degradable compared to the heartwood.